Persistent Photoconductivity in ZnO Nanowires in Different Atmospheres - Davide Cammi; Carsten Ronning (Advances in Condensed Matter Physics)
We investigated the photoconductivity of single ZnO nanowire device as a function of the surrounding atmosphere, considering the comparison between reduced pressure, inert gas environments, and air. We show that after UV excitation the photocurrent persists for hours, in particular in vacuum, nitrogen, and argon. In the presence of oxygen, the photodecay rate is initially fast but then becomes considerably slower, resulting in a long persisting photo-conductivity tail. Our proposed model explains the persistence of the photoconductivity (PPC) in terms of band bending at the surface of the nanowires, which is related to the trapping of electrons from the conduction band.